P65 Sexual behaviour in the time period between being tested for chlamydia and receiving test result and treatment. (18th May 2015) - Harding-Esch, Emma; Sherrard-Smith, Ellie; Fuller, Sebastian Suarez; Harb, Ana; Furegato, Martina; Mercer, Catherine; Sadiq, S Tariq; Howell-Jones, Rebecca; Nardone, Anthony; Gates, Pam; Pearce, Amy; Keane, Frances; et al.
Abstract : Background/introduction: There is a lack of data on the sexual behaviour of patients between being tested for chlamydia, receiving the test result, and being treated. This time-period may be important in the transmission of chlamydia, as infection could continue to be spread to sexual partners whilst awaiting the test result and treatment. Aim(s)/objectives: To investigate the sexual behaviours of patients between the time of being tested for chlamydia and receiving test result and treatment in order to investigate the benefits that a point-of-care test (POCT) might bring to clinical practice. Methods: We conducted a cross-sectional clinical audit of GUM clinic attendees. Clinic staff conducted a notes review of patients returning for chlamydia treatment following a positive chlamydia test result, and of age- and sex-matched chlamydia negatives. The data also served as an audit for the GUM clinics, following BASHH guidelines. Results: Five of nine GUM clinics approached participated, in July–December 2014. Data from 775 patients were included in analyses, 365 of whom were chlamydia-positive. Males with 2–4 partners, and those who reported never using a condom, were more likely to be chlamydia positive. For 21/143 (14.7%) positive patients who provided data, last new sexual contact was in the period between test and treatment. Data were missing on condom use (22%) and recent new partners (81%). Discussion/conclusion: Patients continue to form new sexual partnerships whilst awaiting chlamydia test results, allowing for the possibility of infecting new sexual partners. POCTs which remove the test to treatment delay could prevent this onward transmission.